DEVELOPMENT AND FEASIBILITY TESTING OF THROTTLE-BY-WIRE TRAINER MEDIA IN MOTORCYCLE TECHNIQUE LEARNING (ATIKANOTO: Journal of Automotive Engineering Education, 2025)
This study aims to develop and evaluate the feasibility of a learning media in the form of a Throttle By Wire (TBW) electrical system trainer for motorcycle engineering education. The research employed a Research and Development (RD) approach using the DDD-E model, and its effectiveness was tested through a pre-experimental one-group pretest-posttest design. The research subjects were vocational high school students in the automotive engineering program. The instruments used included expert validation sheets, student response questionnaires, and objective tests to assess learning outcomes. The validation results showed that the TBW trainer was considered very feasible by experts with a 100% feasibility score. Students’ responses were also categorized as very good with an acceptance rate of 78.94%. The paired sample t-test obtained a significance value of 0.000 (≤0.05), indicating a significant difference between pretest and posttest results. The N-Gain analysis reached a score of 0.89, which falls into the high category, demonstrating highly effective improvement in student learning outcomes. Based on these findings, the TBW trainer is proven to be both feasible and effective in enhancing students’ learning achievements. This media is recommended for broader implementation in teaching modern motorcycle electrical systems, particularly to bridge the gap between theoretical knowledge and practical application. Penelitian ini bertujuan untuk mengembangkan dan menguji kelayakan media pembelajaran berupa trainer sistem kelistrikan Throttle By Wire (TBW) pada pembelajaran teknik sepeda motor. Metode penelitian menggunakan pendekatan Research and Development (RD) dengan model DDD-E, yang diuji efektivitasnya melalui desain pra-eksperimental one-group pretest-posttest. Subjek penelitian adalah peserta didik SMK program keahlian teknik otomotif. Instrumen penelitian meliputi lembar validasi ahli, angket respon peserta didik, serta tes objektif untuk mengukur hasil belajar. Hasil validasi ahli menunjukkan bahwa media trainer TBW dinyatakan sangat layak dengan skor kelayakan 100%. Respon peserta didik juga tergolong sangat baik dengan tingkat penerimaan 78,94%. Uji statistik paired sample t-test menghasilkan signifikansi 0,000 (≤0,05), yang menunjukkan adanya perbedaan signifikan antara hasil pretest dan posttest. Analisis N-Gain memperoleh skor 0,89 dengan kategori tinggi, menandakan peningkatan hasil belajar peserta didik yang sangat efektif. Berdasarkan temuan ini, media pembelajaran trainer TBW terbukti layak dan efektif dalam meningkatkan hasil belajar peserta didik. Media tersebut direkomendasikan untuk diterapkan secara lebih luas dalam pembelajaran sistem kelistrikan sepeda motor modern, khususnya untuk menjembatani kesenjangan antara teori dan praktik.